ANALISA KEPUASAN PELANGGAN TERHADAP MUTU PRODUK MAINAN EDUKASI SMART HAFIZ - Masshitah, Sari (EDUTECH CONSULTANT, 2018)
This study was conducted to identify Smart Hafiz product product attributes, measure the level of customer satisfaction with Smart Hafiz product quality, analyze the factors that affect customer satisfaction with Smart Hafiz, determine Smart Hafiz attributes so that customer satisfaction increases. The method of selecting respondents is based on non probability sampling by using purposive sampling, where the respondents selected correctly have criteria as samples with a confidence level of 95%. The primary data in this study were obtained from the results of a closed questionnaire distributed to Al qolam customers and reseller of the EPD Idea team Edo Aprianto with a total of 50 respondents and 22 questions. The results of this study are Smart Hafiz product attributes and can be grouped into 6 quality dimensions. namely the main functions of the product (performance), reliability (aesthetics), aesthetics (aesthetics), conformance (durability), durability (durability) and ability (serviceability). Measuring the level of customer satisfaction obtained by the percentage of customer satisfaction on the quality of Smart Hafiz product attributes is 90.8%, while the percentage of customer dissatisfaction with the quality of Smart Hafiz products is 9.2.0%. Product attributes that are considered to meet customer expectations are Smart Hafiz can stimulate audio children, Smart Hafiz as a support media for parents to educate children, Smart Hafiz reduces children using gadgets, Smart Hafiz stimulates children's visuals, and Smart Hafiz's physical form is neat / smooth.